Julius Kurth 1870-1949 : Berliner Japansammler, Gelehrter und Pfarrer. (Asien- und Afrikastudien der Humboldt-Universität zu Berlin, 2017)
The pastor, collector and scientist Julius Kurth (1870–1949) made a name for himself particularly through his collection of Egyptian cabaret, which is now located at the University of Halle-Wittenberg, and through numerous publications on Japanese woodcuts. While his achievements in the field of Egyptology have already been recognized by archaeologists through an excellent inventory catalogue, a presentation and evaluation of his other achievements was still pending. The volume edited by Hartmut Walravens lists and discusses all of Kurth's publications. Of particular importance are his monographs on the Japanese painters and woodcut artists Utamaro, Harunobu and Sharaku as well as his history of Japanese woodcuts, which appeared in three editions and three large quartz volumes between 1925 and 1929. Kurth, who learned Japanese as an autodidact, had already written a play in 1904, fascinated by the mysterious personality of Sharaku, which is now being published for the first time in this volume. Kurth's own woodcut collection, which formed an important basis for his work, was sold by his heirs. But based on the illustrations and references in Kurth's publications, at least part of the collection can be reconstructed. The volume is supplemented by letters from the illustrator and bookplate artist Franz von Bayros (1866–1924) to Kurth and by a separate contribution by the art historian Setsuko Kuwabara on Kurth's interest in Japanese bookplates.